In-situ measurement of colloidal gold adsorption on functionalized silica surfaces - Mazurenka, M; Hamilton, S; Unwin, P; Mackenzie, S (American Chemical Society, 2008)
Evanescent wave cavity ring-down spectroscopy (EW-CRDS) has been applied to study, in situ, the deposition kinetics of commercially available gold colloids on functionalized silica surfaces from quiescent solution. Neither 5 nor 20 nm citrate-stabilized nanoparticles were observed to adsorb on clean silica surfaces. Adsorption on a poly-l-lysine-functionalized surface, however, occurs readily and irreversibly with the kinetics of adsorption differing markedly for the two particle sizes studied. 5 nm particles adsorb to form a highly disperse submonolayer of individual particles with atomic force microscope images showing no evidence of aggregation. The controlled growth of multilayer nanoparticle/polyelectrolyte films is demonstrated by alternately depositing colloidal particles and poly-l-lysine films. The deposition of multilayer nanoparticle films increases the sensitivity of the functionalized surface to changes in the solvent refractive index. The adsorption kinetics of the 20 nm colloid is more complex than that of the smaller colloid with adsorbed particles acting as nucleation sites for subsequent aggregation with the result that the interfacial absorbance continues to increase indefinitely with time.